2021
DOI: 10.3390/ma14185282
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen-Induced Cracking Caused by Galvanic Corrosion of Steel Weld in a Sour Environment

Abstract: This study examined the hydrogen-induced cracking (HIC) caused by galvanic corrosion of an ASTM A516-65 steel weld in a wet sour environment using a combination of standard immersion corrosion test, electrochemical analyses, and morphological observation of corrosion damage. This study showed that the weld metal has lower open circuit potential, and higher anodic and cathodic reaction rates than the base metal. The preferential dissolution and much higher density of localized corrosion damage were observed in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…Previous studies (Okonkwo et al, 2019) found that in the welded parts of A508 and other series stainless steel areas, the fine-grained region of low-alloy steel near the fusion boundary is the most prone to galvanic corrosion. However, the crack produced by galvanic corrosion may induce crevice corrosion, which intensifies the corrosion of welded parts (Park et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies (Okonkwo et al, 2019) found that in the welded parts of A508 and other series stainless steel areas, the fine-grained region of low-alloy steel near the fusion boundary is the most prone to galvanic corrosion. However, the crack produced by galvanic corrosion may induce crevice corrosion, which intensifies the corrosion of welded parts (Park et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…The article reports the results of the examination of the protective properties of silane coatings based on vinyltrimethoxysilane and ethanol, doped with the following electrolytes: acetic acid, lithium perchlorate LiClO 4 , sulphuric acid H 2 SO 4 and ammonia NH 3 . Park et al [ 10 ] examined the hydrogen-induced cracking caused by galvanic corrosion of an ASTM A516-65 steel weld in a wet sour environment using a combination of a standard immersion corrosion test, electrochemical analyses and morphological observation of the corrosion damage. Wang et al [ 11 ] investigated the effects of Ti and Cu addition on inclusion modification and corrosion behavior in the simulated coarse-grained heat-affected zone of low-alloy steels by using an in situ scanning vibration electrode technique, a scanning electron microscope/energy-dispersive X-ray spectroscopy and an electrochemical workstation.…”
mentioning
confidence: 99%